Early Miocene cartilaginous fishes (Chondrichthyes: Holocephali, Elasmobranchii) from Chile: Diversity and paleobiogeographic implications. (December 2019) - Villafaña, Jaime A.; Nielsen, Sven N.; Klug, Stefanie; Kriwet, Jürgen
Abstract: The early Miocene is characterized by warm conditions until the middle Miocene when temperatures dropped significantly. The presence of tropical to subtropical invertebrate faunas in early Miocene sediments of Chile supports the hypothesis of warm temperatures. The Neogene fossil record of chondrichthyans (holocephalans, sharks, rays and skates) has been well established for Chile. However, most studies focused on middle Miocene to Pliocene records, whereas early Miocene chondrichthyans have been rather poorly investigated up to now. The aim of this study is to describe early Miocene chondrichthyans from Chile and to discuss their paleobiogeographic and ecological implications. Here, we report seventeen chondrichthyan taxa from the early Miocene of Chile. The fauna includes the first fossil record of Mustelus from the Pacific coast of South America, the first oral tooth of Pristiophorus humboldti nov. sp. from the Neogene of South America and the first fossil record of Alopias from the Neogene of Chile. We are able to increase the total number of taxa from the early Miocene of Chile from 13 to 21. Faunal shifts in the marine waters of Chile between the early Miocene and the present reveal different biogeographical dynamics: three taxa decreased their southern latitudinal range, seven increased their southern latitudinal range, six went globally extinct and one went regionally extinct. The extinction and latitudinal changes observed in chondrichthyans can be best explained by climatic fluctuations during the Neogene and Holocene along the Pacific coast of South America. However, studies to evaluate the effect of ecological traits should be considered in the future. Highlights: The total number of taxa from the early Miocene of Chile was increased. First fossil record of Mustelus from the Pacific coast of South America. First fossil record of Alopias from the Neogene of Chile. New species of sawshark Pristiophorus humboldti nov. sp. The chondrichthyan fauna experimented biogeographic changes through the time.